“Socket Lock-it”: tooth extraction socket compression device for special needs patients / Aminda Faizura Omar … [et al.] - Omar, Aminda Faizura; Rosli, Ahmad Syukri; Ismail, Mohd Isyrafuddin; Mohd Suria Affandi, Tun Yasmin Iffah; Husna, Nur Nabilah; Ahmad, Mas Suryalis (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Mechanical pressure is important for bleeding control after tooth extractions as it not only augments the coagulation cascade by constricting blood vessel and stimulating platelet plug formation to occlude blood vessels. This is not always possible in individuals with special needs (IWSN), patients who have no opposing teeth or unable to tolerate suturing. This increases the risk for reactionary or prolonged bleeding. The objective of the “Socket Lock-it” is to compress dental extraction sockets by locking the gauze or pressure packs in place to assure the initiation phase of hemostasis is achieved in the early post-extraction period. Utilising non-plastic materials to be more environmentally friendly, this device has two layers of materials: a soft polyurethane inner layer (1.0mm) for soft tissue protection and hard protective co-polyester outer layer to prevent fracture or breakage in the event the patient bites down. This device provides continuous pressure to extraction sites without the need for compliance. Due to the variation in alveolar ridge sizes, this device is malleable when submerged in hot water and can be well adapted to any size of edentulous ridge. It also comes in various shapes according to the extraction site. A metal dot has been impregnated into the edge of the device to easily detect the device in the event of ingestion or aspiration. Another fail-safe method to prevent aspiration is the addition of a hole at edge of the device to help anchor the device extraorally using floss. This easy-to-use device can be used in by any clinician in both adult and paediatric patients therefore can be commercialised to general dentists and specialists to prevent adverse effects of uncontrolled bleeding. The extended buccal flap not only provide additional retention and but a clear indicator of the direction of the device which can help clinicians effectively use it.